Specificity of IS6110-based amplification assays for Mycobacterium tuberculosis complex. - Hellyer, T J (1996)
The specificity of IS6110 for the Mycobacterium tuberculosis complex has recently been questioned. We observed no cross-reaction with 27 nontuberculous mycobacteria using strand displacement- and PCR-based amplification of the nucleotide 970 to 1026 and 762 to 865 regions of IS6110. These data support use of selected regions of IS6110 as M. tuberculosis complex-specific targets.